2014
DOI: 10.1111/bjso.12086
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of mortality salience and political orientation on moral judgments

Abstract: In two studies, the authors examined how threat induced by reminders of mortality would moderate the effect of political orientation on moral judgments. In Study 1, university students (n = 113) categorized their political orientation, were randomly assigned to complete a fear of death or public speaking scale, and then completed a moral foundations questionnaire. In Study 2, university students (n = 123) rated their political orientations, were randomly assigned to write about their own death or dental pain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…The current findings provide partial support for the positive association between threat salience and endorsement of binding moral foundations, similarly to some past research (Bassett et al, ; Koleva et al, ; Wright & Baril, ; Van de Vyver et al, ). We examined this association using previously underexplored applied field data (real‐life religious sermons being delivered) and have found that the loyalty/betrayal foundation was the only one to be predicted by historical fluctuations in societal‐level threat salience.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The current findings provide partial support for the positive association between threat salience and endorsement of binding moral foundations, similarly to some past research (Bassett et al, ; Koleva et al, ; Wright & Baril, ; Van de Vyver et al, ). We examined this association using previously underexplored applied field data (real‐life religious sermons being delivered) and have found that the loyalty/betrayal foundation was the only one to be predicted by historical fluctuations in societal‐level threat salience.…”
Section: Resultssupporting
confidence: 89%
“…In other words, threatening stimuli, especially those which remind us of our own mortality, would make liberals more liberal and conservatives more conservative (see Greenberg et al, ; Pyszczynski, Rothschild, & Abdollahi, ). There is evidence suggesting that TMT’s predictions apply to moral foundations: Mortality salience was found to increase liberals’ ratings of the individualizing, but not binding, foundations (Bassett, Van Tongeren, Green, Sonntag, & Kilpatrick, ). In short, political conservatism as a motivated social cognition approach suggests that threat salience would bolster conservatism whereas TMT advocates that threat would relatively increase the level of conservatism, but only among those who are already leaning towards conservatism.…”
Section: Moral Foundations and Ideologymentioning
confidence: 99%
“…Importantly, this study represents an important first step toward establishing creative achievement as an anxiety‐buffering mechanism (see Harmon‐Jones et al., ). According to TMT, one way to cope with death awareness is to re‐affirm one's cultural worldviews and beliefs (Greenberg et al., ), for example, by endorsing moral values (Bassett, Van Tongeren, Green, Sonntag, & Kilpatrick, ). To further examine the anxiety buffering properties of creative achievement, it may be useful to focus on creativity‐related worldview defense measures.…”
Section: Discussionmentioning
confidence: 99%
“…A contrasting approach, defined as 'world-view-specific bolstering hypothesis' (Bassett, Van Tongeren, Green, Sonntag, & Kilpatrick, 2014), can be traced back to the theoretical model of dogmatism proposed by Rokeach (1960). Consistent with this perspective, Greenberg and Jonas (2003) suggested that existential and economic stress causes political and ideological radicalization, prompting left-wing people to move to more extreme left positions and right-wing people to move to more extreme right positions.…”
Section: Consequences Of Uncertainty Salience At Group and Intergroupmentioning
confidence: 99%
“…More recently, Bassett et al . () found that mortality salience intensified the moral differences between liberals and conservatives. Despite their differences, these perspectives highlight the importance of considering how pre‐existing opinions and motives might influence responses to situationally induced uncertainty or threat.…”
Section: Introductionmentioning
confidence: 99%